A legal vision in the legitimacy of disciplinary lying - an analytical study in the Iraqi administrative and comparative legislation and the position of jurisprudence and the judiciary - Lecturer, Dr. Haider Najeeb Ahmed, (The college of law and political science journal, 2023)
.